Analisis Produk UMKM Karedok Ibu Darti Kabupaten Bekasi - Nasrun Baldah; Cindy Amalia (LPPM STEBIS YPII, 2026)
The culinary industry in Indonesia, particularly Micro, Small, and Medium Enterprises (MSMEs), plays a vital role in the national economy, contributing 60% to 61% of Gross Domestic Product (GDP) by 2025, with the culinary sector being the largest contributor. Adapting MSMEs to global trends, particularly increasing consumer demand for personalized and innovative culinary experiences, is driving added value to culinary products. One prominent MSME example is karedok, a traditional Sundanese dish rich in nutrients and popular with a modern society that prioritizes healthy eating. This paper analyzes the products and operations of Ibu Darti's Karedok MSME, located in Bekasi Regency. The business, which has been operating for five years, faces challenges in production management, unstructured financial records, and rudimentary human resource management. The study aims to describe the overall business conditions, identify problems, and provide strategic recommendations to support sustainable business